Thermo-Electrochemical Cells Based on Carbon Nanotube Electrodes by Electrophoretic Deposition - Qian, Weijin; Cao, Mingxuan; Xie, Fei; Dong, Changkun (Nano-Micro Letters, 2016)
Drawbacks of low efficiency and high cost of the electrode materials have restricted the wide applications of the thermo-electrochemical cells (TECs). Due to high specific areas and electrical conductivities, the low cost multi-walled carbon nanotubes (MWNTs) are promising alternative electrode materials. In this work, the MWNT films of up to 16 cm2 were synthesized on stainless steel substrates by the electrophoretic deposition (EPD) to make the thermo-electrochemical electrodes. MWNT electrodes based on TECs were characterized by cyclic voltammetry and the long-term stability tests with the potassium ferri/ferrocyanide electrolyte. The TECs reached the current density of 45.2 A m−2 and the maximum power density of 0.82 W m−2. The relative power conversion efficiency of the MWNT electrode is 50 % higher than that for the Pt electrode. Meanwhile, the TECs was operated continuously for 300 h without performance degradation. With the priorities of low cost and simple fabrication, EPD-based MWNT TECs may become commercially viable.